Swine Flu Koirala Surya - Koirala, Surya (Journal of Nursing Education of Nepal, 2023)
Swine flu is a respiratory disease caused by influenza viruses that can be transmitted to humansfrom pigs and result in a barking cough, decreased appetite, nasal secretions and listless behavior.Swine flu viruses may change within one to four days so that they are easily transmissible amonghumans. Symptoms of swine flu in humans are similar to most influenza infections: fever (100F or greater), cough, nasal secretions, fatigue, and headache. The incubation period for the disease is about one to four days. Swine flu is contagious from about one day before the onset of symptoms to about five to seven days after symptoms develops; some patients may be contagious for a longer time span. The disease lasts about three to seven days with more serious infections lasting up to 10 days. It has a devastating effect on the economy and health of the communities even though it can be prevented and controlled with different measures like vaccines and antiviral drugs. The most serious complication of the flu is pneumonia.
Keywords: H1N1 visus; Influenza; PPE; Pandemic; Swine Flu